The Effect of FE, Guava Juice, and Cantaloupe on Hemoglobin Levels in Pregnant Women - Agrisdian, Zerly; Lutfiah, Nita Hasna; Shobirin, Gilang Akbar (STIKES Adi Husada, 2024)
Anemia, characterized by below-normal hemoglobin levels, is a common problem among pregnant women and can have serious consequences if left untreated. Fe (iron) plays a role in increasing hemoglobin synthesis in the body. Giving guava and cantaloupe juice containing vitamin C is expected to increase Fe absorption so that it can increase hemoglobin levels in pregnant women. The type of research used was a quasi-experiment with a pre- and post-test control group research design. The research sample was divided into two groups, namely the experimental group with the treatment of giving Fe tablets accompanied by guava juice and cantaloupe and the control group, which was only given Fe tablets. The number of samples was 18 pregnant women in the second and third trimesters in each group. The study was conducted for 1 month at Mrs. “N” PMB in Mojoagung, Jombang. There is a relationship between the administration of Fe tablets accompanied by red guava juice and cantaloupe in pregnant women, where pregnant women who consume Fe tablets and red guava juice and cantaloupe experience higher hemoglobin levels than the control group who only consume Fe tablets. Consumption of Fe tablets accompanied by guava and cantaloupe juice can increase hemoglobin levels in pregnant women. For further research, lab tests can be conducted to measure vitamin C levels in several juice formulas.